Public Unions Under First Amendment Fire - Tabatha Abu El-Haj (Washington University Law Review, 2018)
Unions today are under First Amendment fire, with the compelled speech doctrine as the weapon of choice. Conservative interests are waging a legal war against agreements that include “fair-share service fees,” under which public-sector unions are permitted to charge nonunion members to pay their share of the costs of collective bargaining. Espousing libertarian theories of free speech doctrine, an array of conservative-funded litigants maintain that fair-share service fees, at least in the context of public-sector unions, constitute a form of political speech, and that laws mandating their payment by nonunion members violate the First Amendment’s prohibition against compelled speech. The Supreme Court is poised to accept this position, having granted certiorari in Janus v. American Federation of State, County & Municipal Employees, Council 31, a case that threatens to overrule the Court’s longstanding acceptance of the constitutionality of fair-share service fees. Notwithstanding the superficial appeal of the compelled speech argument, this Article argues that pro-union interests have plenty of cover within the First Amendment’s freedom of association doctrine. Viewing Janus and its ilk through an associational lens demonstrates the fallacies that lie behind doubts concerning the constitutionality of such agreements. Although it is doubtful that the Supreme Court will reaffirm the constitutionality of fair-share service fees this term, it is important to air such arguments in order to head off potentially even more significant First Amendment attacks on unionism that are currently underway and to articulate a theory of the First Amendment that remains consistent with the basic New Deal compromise that leaves matters regarding labor policy to our legislatures, where they belong.
Keywords: First Amendment; Labor law; Janus v. American Federation; Union law; Freedom of Association; Public-sector unions; Fair-share service fees